Asal Usul Bahasa - Efendi, Erwan; Mubina, Fathan; Syahputra, Roni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Language is the center of human life naturally. The basic function of language is to understand what are the different objects, including the feelings they experience. Limited number of words available to represent objects, words are categories to refer to certain objects: people, things, events, properties, feelings, and so on, not all words are available to refer to objects. In general, verbal language is communication in the form of spoken or written, for example, words spoken directly (speaking) can be done directly (face to face) and through writing. In general, non-verbal language is communication that does not use words, for example, using body language. This study uses the literature study method by examining various references from both books and journals related to social change and education.